Applying the health belief model and theory of planned behaviour to nutrition counselling in malnourished pregnant women in Seyegan, Sleman - Nabilla Ersya Audina (BKM Public Health and Community Medicine, 2021)
Objective: This program was established to improve the performance of the nutritionists of Puskesmas Seyegan in providing nutrition counselling for malnourished pregnant women. This program initiated the arrangement of a nutrition counselling guidebook based on the combination of the health belief model (HBM) dan the theory of planned behaviour (TPB) and its application in nutrition practice. Content: The program was started in September 2020 by arranging a nutrition counselling guidebook based on HBM and TPB to provide clear guidance to the nutritionists in performing counselling. The guidebook was complemented by a nutrition care documentation form and a leaflet referring to the approaches applied. This program targeted the system of the pre-existing program at Puskesmas Seyegan in managing malnourished pregnant women. By strengthening the system, we expected that this program could be sustainable. Within the first month of implementation, 12 malnourished pregnant women were exposed to this program. During the implementation, the nutritionists found that the guidebook was very useful in assisting them to perform nutrition counselling. The nutritionists of Puskesmas Seyegan were very open to new knowledge making it easy to introducing some approaches of counselling that were relatively new for them. However, the lack of collaboration with doctors/midwives caused it a lot more challenging to confirm the women’s attendance to the whole counselling series (3 sessions). Inability to monitor any nutritional status changes was the main issue. Considering the increased risk of low birth weight in neonates born from malnourished pregnant women, we collected the data and found that 7 women (58%) born babies with normal birth weight. In conclusion, the application of HBM and TPB to nutrition counselling could be a potential alternative to strengthen the system of Puskesmas Seyegan in managing malnutrition among pregnant women, if it was supported by a good interprofessional collaboration.